Law Enforcement In The Judge's Verdict Against Narcotics Abuse For Yourself - Puji Andrayani; Rakhmat Bowo Suharto (Universitas Islam Sultan Agung, 2020)
The crime of narcotics abuse is an extraordinary crime, because the impact is very detrimental not only to the user but also the community, so that every crime must be punished, and the law in this case Act No. 35 of 2009 must be upheld. This study aims to identify and describe law enforcement in the judge's decision on the crime of narcotics abusers for oneself from a justice perspective. This study uses a normative juridical approach to analysis descriptive. The data used is secondary data obtained through library research, which is then analyzed qualitatively. The results of this study are that law enforcement in the judge's decision on the crime of narcotics abusers for themselves in the perspective of justice is based on the judge's consideration in determining the severity or lightness of the punishment imposed on the defendant according to the principle of balance between guilt and illegal acts. Narcotics abusers themselves must be viewed as victims, so they must be rehabilitated. Supreme Court Circular No. 4/2010 is used as a reference for judges to determine whether a person is an individual abuser or not. Narcotics abusers themselves must be viewed as victims, so they must be rehabilitated. Supreme Court Circular No. 4/2010 is used as a reference for judges to determine whether a person is an individual abuser or not. Narcotics abusers themselves must be viewed as victims, so they must be rehabilitated. Supreme Court Circular No. 4/2010 is used as a reference for judges to determine whether a person is an individual abuser or not.